The Role of Summary Judgment in Commercial Law - Halligan, Jordan (Victoria University of Wellington Law Review, 2023)
This article considers the historical development of the summary judgment procedure, both in England and in New Zealand, for the purpose of highlighting the commercial imperatives underlying the procedure's genesis. It goes on to discuss the modern role played by summary judgment, by reference to two recent decisions that illustrate the tensions associated with expanding the procedure's scope into previously unheralded areas of the law. It concludes that commercial parties should rigorously consider whether their dispute is capable of being determined by summary judgment, but that this should not be understood as lessening the standard required to be met before judgment will be granted.